Robust Optimal Control of Dynamically Decoupled Systems via Distributed Feedbacks - Dmitruk, Natalia (Optimization in the Natural Sciences, 2015)
We consider an optimal control problem for a large-scale dynamical system represented by a team of objects with linear time-varying decoupled dynamics subject to disturbances and coupling constraints. It is assumed that centralized control is impossible and a delay in the communication network between systems is present. An algorithm for distributed feedback control is proposed. The algorithm breaks the large scale optimal control problem into sub-problems optimizing only for the inputs of the associated system. Feasibility and suboptimality of distributed control for the overall system is established and relevant data to be exchanged between the systems is analyzed.